2015
DOI: 10.1177/0194599815594360
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐Specific Survival with Spindle Cell Carcinoma of the Head and Neck

Abstract: Spindle cell carcinoma carries a worse prognosis than SCC. Larger tumor size, older age, and metastatic disease portend worse survival with SpCC of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 36 publications
3
33
0
1
Order By: Relevance
“…This conclusion, however, may be confounded by the fact that TL is more often performed to remove larger malignant tumors, which carry higher risk. The associations found for other clinical features were consistent with the findings of previous studies, as low tumor differentiation, and higher T, N, and clinical stages all correlated with worse prognoses [15, 16]. …”
Section: Discussionsupporting
confidence: 90%
“…This conclusion, however, may be confounded by the fact that TL is more often performed to remove larger malignant tumors, which carry higher risk. The associations found for other clinical features were consistent with the findings of previous studies, as low tumor differentiation, and higher T, N, and clinical stages all correlated with worse prognoses [15, 16]. …”
Section: Discussionsupporting
confidence: 90%
“…It has been widely investigated and recognized that SpCC has worse prognosis than SCC [15]. Intrinsic tumor properties and lack of standard treatment guidelines may be the possible explanations for the unfavorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there was no difference in the outcome for larynx or hypopharynx site. In his large study analysing 118 patients he identified in multivariate analysis only age, tumour size, and M (metastatic) stage as variables significantly affecting the survival with SpCC [ 19 ].…”
Section: Discussionmentioning
confidence: 99%